2021
DOI: 10.1002/chem.202103234
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of Conjugation‐Ready Repeating Units of Acinetobacter baumannii AB5075 for Glycoconjugate Vaccine Development

Abstract: Acinetobacter baumannii is an opportunistic pathogen that causes serious nosocomial infections. One of the multidrug-resistant strains, AB5075, can result in bacteremia, pneumonia and wound infections associated with high morbidity and mortality. The structurally unique glycans on the surface of these bacteria are attractive targets for the development of glycoconjugate vaccines. Here, we report the first total synthesis of the densely functionalized trisaccharide repeating unit of A. baumannii AB5075 as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Indeed, the lab has developed several synthetic carbohydrate vaccine constructs that are either fully synthetic or produced through semisynthesis. These conjugates were active against a wide range of pathogens, including Acinetobacter baumannii , , Clostridium difficile , Klebsiella pneumoniae , and Streptococcus pneumoniae . …”
Section: Problem Selectionmentioning
confidence: 99%
“…Indeed, the lab has developed several synthetic carbohydrate vaccine constructs that are either fully synthetic or produced through semisynthesis. These conjugates were active against a wide range of pathogens, including Acinetobacter baumannii , , Clostridium difficile , Klebsiella pneumoniae , and Streptococcus pneumoniae . …”
Section: Problem Selectionmentioning
confidence: 99%
“…After 5 minutes, the reaction was allowed to warm to room temperature (18 °C). After 4 h, TLC showed total consumption of starting material 21 b and formation of a less polar spot (22). The reaction flask was transferred into an ice bath then quenched by dropwise addition of 3.0 mL MeOH followed by dropwise addition of water (7.0 mL) until gas evolution stopped.…”
Section: Galnac Thioglycoside 21mentioning
confidence: 99%
“…However, the lack of the appropriate WaaL ligase gene in A. baumannii calls into question whether this was O ‐antigen or perhaps the repeating unit of a capsular polysaccharide [21] . In 2021, Zhang and Seeberger reported the synthesis of trisaccharide repeating units from the CPS of A. baumannii AB5075 [22] . In early 2022, we reported the synthesis of the tetrasaccharide CPS repeating unit from A. baumannii D78 [23] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, more than 20 different A. baumannii polymeric saccharides have been elucidated among more than 90 serotypes [4] . In 2015, Nakamura reported the synthesis of the A. baumannii O18 tetrasaccharide; [5] in 2018, Wu disclosed the semi‐synthesis of a glyco‐conjugate vaccine of A. baumannii strain 54149 and found that pseudaminic acid (Pse) played a critical role in immunogenic activity; [6] in 2020, Gao demonstrated the synthesis of the A. baumannii K47 pentasaccharide using the α‐selective glycosylation method; [7] in 2021, Li and Chen described the synthesis of Pse‐CRM197 conjugates against A. baumannii Infection; [8] in the same year, Seeberger reported the synthesis of the trisaccharide repeating unit of A. baumannii AB5075; [9] one year later, Seeberger published an amazing work on synthetic carbohydrate‐based vaccines against A. baumannii 17978; [10] Yang and Yin reported the chemical synthesis and antigenic evaluation of inner core oligosaccharides of A. baumannii ; [11] recently, Sun described the synthesis of the tetrasaccharide subunit of A. baumannii SMAL, the nonasaccharide of the A. baumannii O22 and the tetrasaccharide fragment of A. baumannii ATCC 17961 [12] . The A. baumannii ATCC 17961 O‐antigen consists of pentasaccharide repeating unit (with core trisaccharide subunit [→6)‐β‐ d ‐Glc(1→3)‐β‐ d ‐GalNAc(1→3)‐α‐ d ‐Gal(1→], β‐linked to a 2,3‐diacetamido‐ d ‐glucuronate at C4‐OH of Gal and β‐linked GlcNAc at C6‐OH of Gal) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%